The pass-through to consumer prices in CIS economies: The role of exchange rates, commodities and other common factors - Mariarosaria Comunale; Heli Simola (Bank of Finland, Institute for Economies in Transition (BOFIT), 2016)
​This empirical study considers the pass-through of key nominal exchange rates and commodity prices to consumer prices in the Commonwealth of Independent States (CIS), taking into account the effect of idiosyncratic and common factors influencing prices. In order to do that, given the relatively short window of available quarterly observations (1999–2014), we choose heterogeneous panel frameworks and control for cross-sectional dependence. The exchange rate pass-through is found to be relatively high and rapid for CIS countries in the case of the nominal effective exchange rate, but not significant for the bilateral rate with the US dollar. We also show that global factors in combination with financial gaps and commodity prices are important. In the case of large rate swings, the exchange rate pass-through of the bilateral rate with the US dollar becomes significant and similar to that of the nominal effective exchange rate.
URN:NBN:fi:bof-201611071479
Keywords: C38; E31; F31; 330